SOCIO-PHILOSOPHICAL INDICATORS AND ASSESSMENT CRITERIA FOR ENSURING HUMAN DIGNITY - Karimov, Gulomnazir Kholmatkhonovich (Oriental Journal of History, Politics and Law, 2026)
This article examines the socio-philosophical essence of ensuring human dignity, its significance in the development of a modern democratic society, and the indicators and assessment criteria used to evaluate the level of human dignity. The study explores the philosophical evolution of the concept of human dignity based on classical and contemporary socio-philosophical theories. The protection of human rights, social justice, civil liberties, access to education and healthcare services, poverty reduction, transparency in public administration, and citizens’ participation in decision-making are systematized as the principal indicators of human dignity. Furthermore, the article provides a comparative analysis of assessment approaches employed by the United Nations within the framework of the Sustainable Development Goals, the Human Development Index, the World Bank, the OECD, and other international organizations, alongside the experience of Uzbekistan. Based on the findings, a socio-philosophical model for assessing human dignity is developed, and scientifically grounded recommendations for its practical implementation are proposed.